Single-cell transcriptomics in bone marrow delineates CD56dimGranzymeK+ subset as intermediate stage in NK cell differentiation - Melsen, Janine E.; van Ostaijen-ten Dam, Monique M.; Schoorl, Dorenda J. A.; Schol, Pieter J.; van den Homberg, Daphne A. L.; Lankester, Arjan C.; Lugthart, Gertjan; Schilham, Marco W. (Frontiers in Immunology, 2022)
Human natural killer (NK) cells in lymphoid tissues can be categorized into three subsets: CD56brightCD16+, CD56dimCD16+ and CD69+CXCR6+ lymphoid tissue-resident (lt)NK cells. How the three subsets are functionally and developmentally related is currently unknown. Therefore, we performed single-cell RNA sequencing combined with oligonucleotide-conjugated antibodies against CD56, CXCR6, CD117 and CD34 on fresh bone marrow NK cells. A minor CD56dimGzmK+ subset was identified that shared features with CD56bright and CD56dimGzmK- NK cells based on transcriptome, phenotype (NKG2AhighCD16lowKLRG1highTIGIThigh) and functional analysis in bone marrow and blood, supportive for an intermediate subset. Pseudotime analysis positioned CD56bright, CD56dimGzmK+ and CD56dimGzmK- cells in one differentiation trajectory, while ltNK cells were developmentally separated. Integrative analysis with bone marrow cells from the Human Cell Atlas did not demonstrate a developmental connection between CD34+ progenitor and NK cells, suggesting absence of early NK cell stages in bone marrow. In conclusion, single-cell transcriptomics provide new insights on development and differentiation of human NK cells.